Mechanisms of innate immunity in pathogenesis of psoriasis: approaches to targeted therapy - E. D. Merkushova (SPb RAACI, 2020)
Psoriasis is a chronic auto-inflammatory, genetically determined dermatosis, being multifactorial by origin, characterized by hyperproliferation of epidermis, affected keratinocyte differentiation and inflammatory reaction in dermis. The disease is characterized by a tendency to spread over the area of lesion, and involvement of articular tissue in the pathological process, which significantly affects the living standards of patients and causes their disability. There are many provoking factors that contribute to occurrence of psoriasis, or progression of existing psoriatic process in individuals with a genetic predisposition. These factors include adverse climatic conditions, skin trauma, exposure to ultraviolet light, burns, infections, etc.This review describes the role of innate immunity in pathogenesis of psoriasis, and describes in detail the mechanisms involved into induction of inflammation of PAMPs and DAMPs. In psoriasis, positively charged catelicidin is considered one of the most important DAMPs, which can form a complex with negatively charged cell polyanions-LL-37/auto-RNA and LL-37/auto-DNA. The interaction of PAMP/DAMP ligands with specific PRR receptors leads to signal activation of effector components of immune system, i.e., assembly of inflammasome complex, caspase activation, synthesis of inflammatory cytokines and processing of their immature forms. The review focuses on the role of TLRs under the conditions of physiological norm, which recognize danger signals and provide protection from pathogens and their timely elimination, and in development of pathological process. Activation of TLRs induces the production of pro-inflammatory cytokines, interferons and antimicrobial peptides, chemokines that support the development of psoriatic inflammation.In addition to TLRs, the mechanisms of involvement of inflammasomes in the development of psoriasis, which provides processing of mature forms of IL-1β and IL-18, are described in detail. Mature forms of these cytokines mediate the development of inflammation in psoriatic focus. In addition, processing of these cytokines by caspases using the positive feedback mechanism provides an additional signal to activate transcriptional activity of their genes and contributes to perpetuated inflammation.The review presents data confirming participation of inflammasomes in the pathogenesis of psoriasis. Much attention is paid to description of pharmacological inhibitors of inflammasomes, which in the future may be the drugs of choice for treatment of inflammatory diseases. The study of molecular mechanisms of the innate immune system will reveal new approaches to prognosis and development of targeted therapy for psoriasis.